Creative Movement and Anti-Gentrification: Learning from Los Tjihapit Market's Coffee in Bandung - Hajaria, Nirmala; Nabila, Adha Ika Putri; Puteri, Lidhiya Ananda Rizki; Syarifah, Maryam Shofi; Ekomadyo, Agus Suharjono (ARCHIHUMANUM, 2024)
The phenomenon of gentrification, driven by the presence of the creative class, is a consequence of the global implementation of the Creative City concept. Bandung has adopted this concept, and one of the areas developed by the creative class is the Cihapit Market area. This article examines how the "creative" community, specifically Kopi Pasar Los Tjihapit, sustains its business amidst gentrification through a placekeeping strategy. Participatory qualitative descriptive research methods were employed to explore the role of architectural space as part of the placekeeping strategy. Five strategies were identified: 1) zoning to support maintenance, 2) collaboration spaces for various partnerships, 3) space flexibility through collective decision-making, 4) collaborative spaces to encourage community involvement, and 5) coordination of all aspects to preserve the public market character. In conclusion, the success of creative placekeeping strategies in architectural spaces combines non-technical aspects such as community enthusiasm with technical aspects such as the arrangement of physical architectural elements.